PENGARUH KOMUNIKASI DIALOGIS TERHADAP KEPERCAYAAN PADA PEMERINTAH - Hastrida, Andhini; Hendriyani (Jurnal Studi Komunikasi dan Media, 2023)
One of the efforts made by government to gain the trust of public is through the use of social media to communicate directly with public. In a democratic country, public trust in government is an important thing needed as capital that enables the successful work of government. This article discusses the influence of mutuality orientation and climate of openness factor in the government's dialogic communication through social media on trust in government. Measurement of the influence of dialogic communication is carried out using a measurement scale for the concept of organization-public dialogic communication (OPDC) which has been adapted for use in social media, while trust in the government is measured using the concepts of competence, benevolence and honesty. This research is an explanatory quantitative research conducted through an online survey of 350 social media followers of the Ministry of Manpower of the Republic of Indonesia. The results of the study show that there is a significant influence of orientation of mutuality and climate of openness factor in dialogic communication through social media on trust in government, and that the climate of openness factor influences trust in the government more than the orientation of mutuality factor.